1971
DOI: 10.1037/h0030853
|View full text |Cite
|
Sign up to set email alerts
|

Relationship factors in desensitization: A persistent trend.

Abstract: The persistent theme contending that relational factors are relevant to the outcome of behavior therapy necessitated the replication with adequate controls of a previous study by these authors. The aim of the study was to explore the relevance to the outcome of desensitization of same-sex and opposite-sex pairings of subjects and experimenters. Twelve groups, consisting of all subjectexperimenter same-or opposite-sex combinations were employed. Confirming the findings of the earlier work that subject-experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1973
1973
1981
1981

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…The sex interaction finding in this study is not in agreement with those of three desensitization studies that attempted to deal directly with sex differences (Cotler, 1970;Nawas & Pucel, 1971;Pucel & Nawas, 1970). Those studies, all of which reported no sex differences, employed automated treatments involving minimal counselor interaction in the treatment of snake phobia.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The sex interaction finding in this study is not in agreement with those of three desensitization studies that attempted to deal directly with sex differences (Cotler, 1970;Nawas & Pucel, 1971;Pucel & Nawas, 1970). Those studies, all of which reported no sex differences, employed automated treatments involving minimal counselor interaction in the treatment of snake phobia.…”
Section: Discussioncontrasting
confidence: 94%
“…"Counselor present" treatment, which allows more opportunity for awareness and interaction, provides a more stringent testing of the sex variable. While dismissing sex pairing as a variable, Nawas and Pucel (1971) built a case for relational factors (involvement, expectancy, subject effort, counselor attention) as "confounding variables" in desensitization that, nevertheless, "approximate the real-life ongoing interactional clinical process of psychotherapy" (p. 242). It does not seem reasonable to exclude sex as a relational variable in the interaction when one considers the research in sex role perception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the absence of a therapist rules out therapist effects, once he is present, he may well affect (for either good or ill) even a process which could have been set up to run without him. Similarly, the absence of sex-pairing effects in desensitization (Nawas & Pucel, 1971) is poor evidence against the sort of relationship factors implied by the Vitalo and the Mickelson & Stevic studies. Indeed, Morris & Suckerman (1974a, b) have demonstrated the effect of therapist warmth on the effectiveness of systematic desensitization, whether this is carried out 'live' (Morris & Suckerman, 1974u), or by an automated procedure with a pre-recorded therapist (Moms & Suckerman, 1974b).…”
Section: Further Implications For Clinical Workmentioning
confidence: 97%
“…The "active ingredient" of relationship in both schools is the same, we believe, despite the difference in concentration of effort. Nawas and Pucel (1971) conducted an experiment testing for the relationship factors operating in systematic desensitization. Working with snake phobias, they divided their subjects into three treatment groups.…”
Section: Relationship and Reinforcementmentioning
confidence: 99%